Geographies of marketisation in English higher education: territorial and relational markets and the case of undergraduate student fees - Hall, Sarah (Wiley, 2015)
In this paper, I use the case of the marketisation of higher education in England to contribute to the growing interest in placing markets, and processes of market making, more centrally within economic geographical research agendas. In particular, my argument focuses on the spatiality of marketisation through the specific case of the introduction of undergraduate student fees in England from 1998 onwards. I argue that the marketisation of English higher education has operated, implicitly at least, with a territorial logic in which students fees are justified through an assumption that the value of a degree from an English university will arise from graduate salary premiums in domestic graduate labour markets. However, I demonstrate how English higher education overflows this territorial framing through the internationalisation of student choice and graduate labour markets in ways that challenge the marketisation process itself. This analysis reveals the hitherto comparatively neglected role of extra- territorial relations in marketisation and the importance of these geographies for the future marketisation of higher education.